Pengembangan Aplikasi Identifikasi Lagu Berbasis Kognitif Menggunakan Model Prototype - Asep Subarkah; Agung Rizal Suryo Laksono; Syahrulloh Syahrulloh; Sunariyo Sunariyo; Yulianti Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
Now with the application of Snap videos or short videos, both those obtained from social media such as Instagram, Twitter, and Facebook, there are many pieces of audio and video files of short duration which contain songs that have meaning. When we are interested in knowing a song, we have a hard time finding out the title of the song or the source. We designed an application to identify cognitive-based songs using a prototype method to overcome these problems. The method we use is a prototype model, this method is a paradigm in software creation and development, we chose this method because the process is relatively faster because it uses mock ups in its application. From the test results, the song identification application that we made is very effective for identifying the types of songs with slow genres such as jazz, blues, and acoustic but less effective for hard rock and RnB songs.